Lithuanian Language at School: Scientific Insights and Pedagogical Experience - Gudzinevičiūtė, Ona Laima; Maskuliūnienė, Džiuljeta (Lietuvių kalba, 2024)
The article reviews the issues investigated in the reports and articles developed from the conference reports of the scientific and practical conferences “Mother Tongue at School” organised at Šiauliai University (since 2021, Šiauliai Academy of Vilnius University) in 2012–2022. The aim of the article is to present the journal “Gimtoji kalba mokykloje” [Mother Tongue at School] using the descriptive-analytical method, to discuss topics, problems, aims of the articles, and to summarise the most relevant issues of Lithuanian studies, Lithuanian language and literature teaching (didactics), variations in the Lithuanian language, changes, standardisation, and the importance of Lithuanian literature in developing a thinking and reading individual, conscious of the importance of the native (Lithuanian) language.The journal “Gimtoji kalba mokykloje” has published 119 articles by 148 authors. Linguistic articles among them are divided into the following thematic blocks: 1) The importance of the influence of linguistic environment and personalities in preserving national identity. Language policy; 2) Public language. Language etiquette; 3) Language in the digital space, computer literacy. Office, administrative language. Language management; 4) Language correctness. Literacy. Spelling and punctuation issues; 5) Language norms and errors; 6) Dialect studies; 7) Stylistic figures. Conceptual metaphors. Associations; 8) Terminology issues; 9) Language didactics. Academic, professional language. The field of topics is broad, discussions include: general language, dialects, language norming, language in the digital space, language didactics, the process of language teaching and learning, and the effects of bilingualism. The articles in the literature section are divided into five thematic blocks: 1) Promotion of reading, professional press for teachers; 2) Lithuanian writers’ works in school, concerns of reading classics; 3) Children’s literature and school; 4) Working with the text to prepare the future reader; 5) Non-traditional literature teaching methods and other problems. Researchers and teachers are interested in current school (and societal) issues, exploring why reading is low and discussing what could encourage reading. The importance of creative, innovative library work and family reading traditions are highlighted. It stresses that the school is also an important player in this field, where the child must become a competent reader.The articles published in the journal encourage a theoretical dialogue between researchers and practical educators, highlight topical issues in teaching Mother Tongue, and invite to jointly search for solutions to problems.
Keywords: Lithuanian language and literature at school; scientific practical conferences; scientific insights; pedagogical experience; journal “Gimtoji kalba mokykloje”; [Mother Tongue at School]